2015
DOI: 10.1111/tme.12202
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of human Herpesviruses types 1–6 and 8 among Greek blood donors

Abstract: HHV-4 DNA is commonly detected in whole blood specimens of healthy individuals. HHVs types 5, 6 and 8 are rarely detected. However, the existence of a donor sample with high HHV-6 viral load raises questions regarding the potential risk of HHV-6 blood-borne infection and the safety of blood products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
6
1
Order By: Relevance
“…In turn, immune activation may stimulate subclinical reactivations of CMV. Accordingly, prevalence of CMV DNA in studies of HIV patients (15.8-42.2%) was high [56][57][58][59] when compared to studies of CMV DNA in healthy controls [60][61][62], though we find no studies where patients and controls were assessed in parallel. This could increase the prevalence and severity of inflammatory disorders linked with CMV.…”
Section: And Inflammagingcontrasting
confidence: 57%
“…In turn, immune activation may stimulate subclinical reactivations of CMV. Accordingly, prevalence of CMV DNA in studies of HIV patients (15.8-42.2%) was high [56][57][58][59] when compared to studies of CMV DNA in healthy controls [60][61][62], though we find no studies where patients and controls were assessed in parallel. This could increase the prevalence and severity of inflammatory disorders linked with CMV.…”
Section: And Inflammagingcontrasting
confidence: 57%
“…Among 176 Japanese pediatric patients visiting medical facilities for various reasons, HHV-6 DNA was detected in four (2.2%) whole-blood samples (55). The prevalence of HHV-6 DNA detection among blood donors was estimated to be 3.5% in a Greek cohort of 401 subjects and 6.1% in a cohort of 198 subjects from Burkina Faso (56,57). Metagenomic analysis of whole-blood samples of more than 8,000 individuals considered healthy revealed the identification of HHV-6A and HHV-6B in 1.5% and 5% of individuals, respectively (30).…”
Section: Dna Viruses Double-stranded Dna Virusesmentioning
confidence: 99%
“…The prevalence of iciHHV-6 appears to vary by country and region (Tanaka-Taya et al, 2004;Leong et al, 2007;Hudnall et al, 2008;Bell et al, 2014). In a previous study we have suggested that the prevalence in Greece is 1 of 401 or 0.25% (Rouka & Kyriakou, 2015). Immunocompetent individuals with iciHHV-6 have high levels of HHV-6 DNA both in cellular and non-cellular samples (Leong et al, 2007).…”
Section: Dear Sirmentioning
confidence: 96%
“…In a previous study we have suggested that the prevalence in Greece is 1 of 401 or 0.25% (Rouka & Kyriakou, 2015). Immunocompetent individuals with iciHHV-6 have high levels of HHV-6 DNA both in cellular and non-cellular samples (Leong et al, 2007).…”
Section: Dear Sirmentioning
confidence: 98%